A comparison of anthropometry and physiological characteristics of finswimming athletes on short and long distance numbers - Safei, Imam; Bahri, Samsul; Resmana, Dadan (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Research on the comparison of physiological characteristics of Finswimming athletes at short and long-distance numbers has not been widely conducted. Therefore, the objective of this research was to determine the differences in anthropometry and physiological characteristics of Finswimming athletes at short and long-distance numbers. This research used an observational research method with a quantitative approach. The subjects of this research were 24 finswimming athletes consisting of 12 long-distance athletes and 12 short-distance athletes with an average age of 17.08 ± 1.03 years; height, 168.55 ± 3.81 cm; and weight, 63.75 ± 6.67 kg; BMI, 22.14 ± 2.96 kg/m2. The results showed significant differences between long-distance athletes and short-distance athletes on BMI variables, total fat, total muscle mass, and VO2max (p <0.05). In detail, long-distance Finswimming athletes had better anthropometry and physiological characteristics when compared to short-distance Finswimming athletes. The results of this research can be used as references for training programs and considerations in talent scouting.